Complications of Cesarean Birth: Clinical Recommendations for Prevention and Management. Issue 2 (March 2020) - Burke, Carol; Allen, Roma
Abstract : Abstract: The increase in severe maternal morbidity and mortality in the United States correlates with a significant rise in U.S. cesarean birth rates from 5.5% in 1970 to a rate of 31.9% of all births in 2018, far beyond the World Health Organization goal of 10% to 15%. Three key contributors to maternal morbidity and mortality related to cesarean birth include complications of hemorrhage, surgical site infection, and venous thromboembolism. All women should be screened for risk factors associated with these major complications during the antepartum, intrapartum, and postpartum period to assure the availability of immediate resources based on the assessment. Implementing evidence-based maternity care safety bundles, toolkits, and protocols to manage these complications can reduce adverse outcomes. Abstract : Maternal morbidity and mortality is significantly increased with cesarean birth as compared to vaginal birth. In this clinical review, strategies for prevention and management of three complications of cesarean birth are presented; postpartum hemorrhage, surgical site infection, and venous thromboembolism. Pertinent patient safety bundles, toolkits, protocols, and national standards and guidelines are applied to care of women having cesarean birth.